THE CONSTRIBUTION OF VILLAGE TOURISM IN INCREASING INTER-REGIONAL COMMUNICATION - Agus Triyono; Suhariyanto Suhariyanto (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
The existence ofthe village has an important role in tourism today. Many rural areas are far from the city’s noise has a natural feel that has been transformed into an area with tremendous value. Various circles trying to find such those areas in order to enjoy the beautiful scenery that they rarely found in the cities. The villages are not only having a natural beauty, but also having people with strong traditions, culture and heritage, as well as their hospitality to all people. They are able to provide a verbal and non verbal information and communication without differentiate each of other. They don’t consider to whom they speaks, does not care about race, ethnicity, religion, or even class. They only provide an open communication without asking a reward. Each village tourism has a various natural resources that is rarely owned by other village tourism. Each village tourism also has its own unique characteristics that are attractive to be visited. The interesting thing that owned by villagetourism is a heritage, such as various types of traditional toys like Grobak Sodor, Dakon, Petak Umpet, Sunda Manda and many other. Those types of toys become a part of village tourism that are able to deliver the communication into the public at large and show that a village has a various natural resources that able to communicate and give a contribution in the tourism area.